Ultrastability of metallic supercooled liquid induced by vibration. (15th March 2021) - Zhao, H.; Sun, F.; Li, X.; Ding, Y.; Yan, Y.Q.; Tong, X.; Ma, J.; Ke, H.B.; Wang, W.H.
Abstract: The range of supercooled liquid region (Δ T ) is the key parameter for evaluating the thermal stability and glass-forming ability of metallic glasses. The enhancement of Δ T is of significance not only for the glass formation and stability, but also for their thermoplastic forming ability. Traditional approaches to increase Δ T are composition regulation or dynamical modulation, which are either time-consuming or difficult to be controlled. Here, through a high-frequency ultrasonic vibration treatment, we show that the Δ T of a La-based metallic glass can be significantly widened from 64 K to 83 K, around 30% increment. This behavior is physically originated from the denser atomic packing and a lower stable basin in the energy landscape induced by the ultrasonic vibration energy. This work might provide a ready route to stabilize the supercooled liquid and glass, and give an insight into the understanding of the glass-forming of amorphous materials. Graphical abstract: Image, graphical abstract